Shifting the center to the margin: online learning and systems of control - Muffoletto, Roberto (Wydawnictwo Naukowe UAM Poznań, 2008)
This essay will argue that before we can fully understand the potential of the existent and emerging communication and information technologies for online distance education, we need to consider their impact on schooling, teaching and learning. The conversation on distance education must be grounded in the historical, social, economic, and political interests related to developed and emerging networked digital systems that guide the visions and definitions of education, if not reality. Not to do this, will continue to repeat the past, the unfulfilled promises of education and media, and to relive history. To accomplish this is no simple matter, for to unpack and understand reality, its history and current practices, and to break from the common-sense discourse on schooling, is complex and demanding. It might be best said that this essay will stake out the territory, the map to be covered, and not provide answers to questions that need to be asked. Even though the perspective offered is one informed through experiences and reflections with the educational system found in the United States, there are similarities found in most western countries. In the end, this essay will consider two paths for education relative to networked digital media and Internet based distance education.